Para além do visível : a virada educacional e o ensino da arte no contemporâneo - Azevedo, Fabianne Chrystianne de (2017)
In order to expand discussions between art and education, this study aims to bind pedagogical strategies adopted on the phenomenon of Educational Turn in the Art Field with visual art teaching in Brazil in the contemporary time. For this purpose, based on the French semiotic, specially sense generators and interaction regime, take as theoretical corpus two target texts about the Educational Turn, “How do you bring a classroom to life as if it were a Work of Art?”, by Claire Bishop, from the book Artificial Hells- Participatory Art and the Politics of Spectatorship and the third chapter of Mônica Hoff Gonçalves' dissertation, named “Educational Turn and Brazilian Art Context”. Starting from semantic categories comprehended from this mentioned analysis, on a second moment, it examines theoretical and practical productions in a scientific article format by academic researchers who make their experiences available on the National Association of Art Researches proceeding events (ANPAP – Visual Arts Educational Committee and Thematic proposed Symposium). With all these, it aims to realize reverberations of problematizations presented on Educational Turn and their appropriations by Art Teachers trainers in Brazil nowadays. 49 articles were assessed and it is possible to observe that the practice of academic researchers is in full dialogue with current artistic productions which work with education on their poetic action.